Morphometric Analysis of Dry Adult Human Mandibular Ramus - Hoque, Md Mesbahul; Ara, Shamim; Begum, Shahanaz; Kamal, AHM Mostafa; Sayeed, Sharmina (Bangladesh Journal of Anatomy, 2015)
Context: Mandible is the lower jaw bone providing attachment of muscles of mastication and facial expression and provides pathway for inferior alveolar nerve and vessels. The mandibular ramus is almost vertical in adult but more oblique in old age. The anterior part of ramus can be used as the donor site for reconstruction of small bone defects in the oral and maxillofacial region. A relatively short mandibular ramus may be an important unfavorable anatomic factor in difficult laryngoscopy. The aim of this study was to determine the morphometry of mandibular ramus from various anatomical landmarks in one hundred eighty five dry adult human mandibles. Materials and Methods: A cross-sectional, analytical type of study was conducted in the department of Anatomy, Dhaka Medical College, Dhaka from July 2010 to June 2011. Morphometry of mandibular ramus was measured with the help of digital sliding calipers. Results: The mandibular ramus was at the same distance from each landmark on both sides demonstrating symmetry. There was no significant difference in the values on the right and left sides of the mandibles. Conclusion: Anatomical knowledge of this study might be useful in certain surgical procedure. DOI: http://dx.doi.org/10.3329/bja.v12i1.22612 Bangladesh Journal of Anatomy, January 2014, Vol. 12 No. 1 pp 14-16